A Pediatric Case Report of Acute Torticollis Secondary to Atraumatic Cerebellar Hemorrhage - Jan Aldrin Enabore; Robert Vezzetti; Guyon Hill (Clinical Practice and Cases in Emergency Medicine)
Introduction: There exists a wide differential of etiologies for pediatric torticollis that extends beyond musculoskeletal factors. Case Report: We present a novel case of a pediatric patient with an acute atraumatic hemorrhage of the left cerebellum presenting with gradual worsening torticollis. Upon further diagnostic workup, he was found to have an intracerebral hemorrhage due to a cerebellar cavernous malformation. Although the hemorrhage boundaries were extensive, the patient had only exhibited transient dysmetria and facial weakness, with ultimate resolution of torticollis and these neurological symptoms after several days. Conclusion: This case demonstrates the importance of maintaining a broad differential in the workup of acute pediatric torticollis.